Creative Thinking Skills of Biology Education Students in a Gender Perspective - Anita Rosiyanti; Nur Endah Susilowati (Women, Education, and Social Welfare, 2025)
Creative thinking represents a crucial twenty-first-century skill that enables learners to generate original ideas, explore diverse perspectives, and develop innovative solutions to problems. This study aims to analyze the creative thinking skills of biology education students at UIN Raden Intan Lampung through a gender perspective. Using a descriptive qualitative design, the research involved a population of 87 students, with a purposive sample of male and female students from the 2021 cohort. Data were collected through an essay-based creative-thinking test adapted from validated instruments covering four indicators: fluency, flexibility, originality, and elaboration. The findings show that female students demonstrated higher mean scores in fluency (58%) and elaboration (49%), while male students scored higher in flexibility (52%) and originality (46%). Overall, students’ creative thinking skills fell into the “moderately creative” category across all indicators. The results highlight the importance of gender-responsive strategies in science education that nurture creativity, inclusivity, and equal opportunity in academic settings. The implication of this study suggests that biology educators should design learning environments that provide balanced opportunities for both genders to express, explore, and refine their creative potential in the context of higher education.